Physics at surfaces and interfaces : (World Scientific, 2003)
This book contains articles in several areas involving a dominant role of surfaces and interfaces. It is divided into four sections. The first section deals with theoretical and experimental aspects of the structure and morphology of clean surfaces and adsorbed layers on surfaces. The next section concerns growth on surfaces leading to semiconductor devices with quantum well, quantum wire and quantum dot structures; also deals with spin transport in 2DEG. Section 3 is on layered synthetic microstructures (LSMs). Analysis of interface roughness and layer composition of LSMs by X-ray techniques, fabrication of hard X-ray telescopes with LSMs, and diffusion across interfaces of LSMs are discussed here. The last section contains articles dealing with semiconductor surfaces exposed to ion beams and ion-irradiated semiconductor multilayers.